OPTIMIZATION OF SINGLY REINFORCED BEAM DESIGN USING SIMULATED ANNEALING - SIMON OLAYIWOLA ADEREMI OLAWALE; OLUTOSIN PETER AKINTUNDE; MOSES OLADIPUPO AFOLABI; OLUWOLE AKINYELE AGBEDE; OLUSOLA OLAYEMI FADIPE (Journal of Engineering Studies and Research)
This paper investigated the optimization of a singly reinforced concrete beam using the simulated annealing. The enhancement of minimum cost of structures and the adoption of the algorithm method of simulated annealing were projected in resolving the complications of constraints associated with optimization problems. The variables are the width, depth, compression steel, tension steel, and cost. The constraints are steel ratios, ultimate moment of resistance, maximum and minimum area of reinforcements while materials costs are considered as the objective function. It is demonstrated that using the concrete compressive strength of 25MPa, simulated annealing can be used to optimize the design of concrete beams effectively. The results also indicate that the complications connected to the actual and genuine evaluation of costs of structures and the connectivity with the compulsory restraints can be adequately resolved using this method.